Functional fitness norms for community-dwelling older adults in Hong Kong. (July 2016) - Chung, Pak-Kwong; Zhao, Yanan; Liu, Jing-Dong; Quach, Binh
Highlights: Functional fitness norms for independent Hong Kongese older adults are established. Ageing-associated degradations were observed in most functional fitness components. No sex differences were reported in BMI and static balance with eyes open. 70 and 75 years would be turning points for different functional fitness components. Abstract: Objective: This study aimed to establish normative data for older adults in Hong Kong and explore age and sex differences in functional fitness. Methods: A sample of 944 independent community-dwellers, aged 65–74 years, was evaluated using the Senior Fitness Test battery in addition to hand grip and single leg stance tests. Normative data were reported for the 10th, 25th, 50th, 75th, and 90th percentiles in 5-year age groups. Results: Except for upper extremity muscle strength in women and body mass index (BMI) in both sexes, ageing-associated degradation was observed in all testing parameters especially in flexibility, balance, and agility. Significant sex differences were found in all testing parameters with the exception of BMI and static balance with eyes open. Moreover, men demonstrated higher capacities for muscle strength, agility, balance, and aerobic endurance, whereas women showed superior flexibility. Conclusion: The normative values enable the evaluation of individual performance regarding the fitness status of older adults in Hong Kong.